PWE-280 Faecal occult blood testing (FOBT) and interval bowel cancers-results of a multicentre study. (22nd June 2015) - George, AT; Aggarwal, S; Menon, A; Dube, M; Vogler, M; Logan, R; Field, A
Abstract : Introduction: We aimed to assess the incidence and demographics of interval cancers (cancers diagnosed within 2 years of a negative FOBT screening) in the eligible population of the East Midlands region. Method: The National Bowel Cancer Audit Programme data from three centres (Queens Medical Centre, Nottingham; Royal Derby Hospital and Sherwood Forest Hospitals) for all colorectal cancers in the screening age group (60–74 years)over a 2-year period (August 2011–August 2013) were linked for their FOBT screening status (BCSP database/Eastern Hub). Three cancer groups were identified: interval cancers, screen detected (positive FOBT) and those in the non-uptake group (eligible patients who declined screening). Tumours at and distal to the splenic flexure were classed as left sided tumours. Dukes C and D tumours were classed as advanced tumours. All three centres were in incident rounds of screening. Results: Of the 521 colorectal cancers identified, 128 (25%) were interval cancers, 162(31%) were screen detected and 231 (44%) were from the non-uptake group. Gender, ethnicity and Deprivation index were comparable between the three groups. The mean age in the interval cancer group was greater (67 yrs) compared to the screen detected (66 yrs) ( p = 0.005 ). The interval cancer group had a higher incidence of right sided cancers (38% vs. 25% and 29%; X 2 =6.59; p = 0.033) compared to the screen-detected and non-uptake groups. Cancers detected in the interval cancer group were of a more advanced stage (Dukes C/D) (70% vs. 34% and 54%; X 2 =37.2; p < 0.005 ) in comparison to screen-detected and non-uptake groups. The one year mortality in the interval cancer group (16%) was higher than the non-uptake group (12%) and the screen detected group (3%) (16%vs12% and 3%; X2=13.8; p < 0.005 ). Conclusion: A quarter of colorectal cancers identified in our screening-eligible population were interval cancers. We highlight the probability that these cancers were 'missed' by the guaiac-based FOBT screening tests. The interval cancer group also had poorer outcomes when compared to the screen-detected group. We highlight the need for a test with a lower false negative rate for population based FOBT screening. Disclosure of interest: None Declared.